Efektivas Reses Ketua Dprd Kota Mataram Dalam Menyerap Dan Merespons Aspirasi Publik - Muhammad Aprian Jailani; Muliani, Muliani; Suci Arliani; Soniati; Rahmad Hidayat (LPPM STISIP IMAM BONJOL, 2025)
This study aims to analyze the effectiveness of the recess program conducted by the Chairman of the Mataram City Regional House of Representatives (DPRD) in absorbing and responding to public aspirations, emphasizing accountability and transparency as the main pillars of effective legislative governance. Using a descriptive qualitative approach, data were collected through in-depth interviews with the Chairman of the DPRD as the key informant and participatory observations during recess activities in various electoral districts. The findings indicate that recess functions not only as a constitutional obligation but also as a participatory democratic tool that bridges the gap between the public and policymaking. The Chairman of the DPRD, Abdul Malik, has made efforts to establish inclusive communication, although challenges such as limited time, budget constraints, and regulatory issues persist. The effectiveness of the recess largely depends on the level of public participation, accountability in reporting, and transparency of information, wherein public aspirations are integrated into regional development planning through the “pokok-pokok pikiran” (legislative input mechanism). This study recommends strengthening the follow-up mechanism, enhancing transparency in reporting, and increasing active public engagement to ensure that recess serves as a substantive and impactful instrument of public representation in regional development policy.